Creativity and Reading Literacy Effects on Fourth Grade Learning Outcomes: An Experimental Study - Asan Basri; Sumanti Sumanti; Siti Aisyah (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Elementary education constitutes a critical foundation for students' academic and cognitive development, where the interplay between creativity and reading literacy has been increasingly recognized as essential determinants of learning achievement. This study investigated the effects of creativity and reading literacy on the learning outcomes of fourth-grade students at Sekolah Dasar Negeri 96/III Bunga Tanjung. A quantitative research design with an associative-predictive approach was employed, involving 28 fourth-grade students as research subjects. Data were collected through validated questionnaires and reading literacy assessments, subsequently analyzed using multiple linear regression. Results indicated that both creativity and reading literacy exerted significant positive effects on student learning outcomes, both partially and simultaneously, with reading literacy emerging as the stronger predictor (β = 0.52) compared to creativity (β = 0.38), and both variables jointly explaining 58.7% of the variance in academic performance (R² = 0.587). These findings suggest that cultivating creativity and reading literacy in early education is imperative for improving students' overall learning outcomes.